The answer would be C and D; the squares will be the base of the pyramid as the triangles are placed on each of the square’s sides to compose the 3D square pyramid
Answer:
x = 9 , y =3
Step-by-step explanation:
-3x + y = 0 ---- 1
2x -2y = -12 -----2
By elimination method:
let's first eliminate x
we can do that by making x equal in both equations
multiply equation 1 by 2 ( because 2 is the coefficient of x in equation 2 and remember we want to equate both equations)
multiply equation 2 by -3 ( because -3 is the coefficient of x in equation 2 and remember we want to equate them both)
-3x + y = 0 ×2
2x -2y = -12 ×-3
-6x + 2y = 0 ----3
-6x + 6y = 36 -----4
subtract equation 4 from 3
that will give
0-4y = -36
which is
-4y = -36
divide both sides by coefficient of y which is-4
(-4y) ÷ (-4) = (-36)÷(-4)
answer : y= 9
substitute 9 for y in equation 1
-3x + y = 0
-3x + 9 = 0
subtract 9 from both sides
-3x +9-9= 0-9
-3x = -9
divide both sides by coefficient of x which is-3
(-3x)÷(-3) = (-9÷-3)
x = 3
Answer:
6
Step-by-step explanation:
![a^{2}+b^{2} =c^{2} \\\\8^{2}+b^{2} =10^{2} \\64+b^{2}=100\\b^{2}=36\\\sqrt{36} =6\\b=6](https://tex.z-dn.net/?f=a%5E%7B2%7D%2Bb%5E%7B2%7D%20%3Dc%5E%7B2%7D%20%20%5C%5C%5C%5C8%5E%7B2%7D%2Bb%5E%7B2%7D%20%3D10%5E%7B2%7D%20%20%5C%5C64%2Bb%5E%7B2%7D%3D100%5C%5Cb%5E%7B2%7D%3D36%5C%5C%5Csqrt%7B36%7D%20%20%3D6%5C%5Cb%3D6)
Answer:
H (the second graph)
Step-by-step explanation:
First we solve this equation:
x = cos^-1(0) = pi/2 and 3pi/2
Now, this is the answer for angles between 0 and 2pi
but there are "negative angles" and angles larger than 2pi
so the general solution that includes all of these cases is:
x = pi/2 + n*pi
here n is any integer.